LIE IN MARK HADDON’S NOVEL THE CURIOUS INCIDENT OF THE DOG IN THE NIGHT-TIME - Fadil Muhammad; Pardi Pardi (Universitas Islam Sumatera Utara, 2020)
This research aims to analyze lie and types of lie in Mark Haddon’s novel entitled The Curious Incident of The Dog in the Night-Time. The fifteen-year-old narrator of the story, Christopher John Francis Boone discovers the slain body of his neighbor’s Poodle Wellington, on the neighbor front lawn, one evening and sets out to uncover the murderer. His investigation is at times aided, and at other times hampered, by the mild form of Autism he lives with. Christopher has a certain character. He finds difficulty in his social interaction; be it in his appearance, language attitude, or thinking. In addition, Christopher has an intelligent ability. He is able to interpret objects around him well. The novel ends with Christopher planning to take A-level exams in physics and further math, and then attend a university in another town. The method of the data analysis in this research uses descriptive qualitative method, and the theory applied in this research was following Bryant (2008) who divided lie into 3 types, i.e. real lies, white lies, and gray lies. The research result shows that all the three types of lie proposed by Bryant are vividly reflected by Christopher in the novel.